FRI0083 Adjustment of the threshold may improve cardiovascular risk stratification in patients with rheumatoid arthritis. (12th June 2018) - Velmakin, S.; Troitskaya, E.; Villevalde, S.; Kobalava, Z.
Abstract : Background: Rheumatoid arthritis (RA) is associated with increased cardiovascular (CV) risk. Besides monitoring of the disease activity, identification of high CV risk patients is of great importance 1, 2 . Objectives: The aim of the study was to assess the abilities of 3 risk models (SCORE, QRisk 2 and 10 year ASCVD) in detecting high CV risk RA patients. Methods: 56 patients with RA (ACR/ EULAR 2010 without known CV disease were examined (84% females, age 58.4±14.1 (M±SD) years, BMI 26.1±5.4 kg/m 2, smokers 9%, arterial hypertension (AH) 64%, dyslipidemia 57%, diabetes 7%). Median duration of RA was 7 years (IQR 2–14). Seropositive RA was diagnosed in 73% of patients. Median hsCRP was 7.8 mg/dl (IQR 2;21.4), rheumatoid factor (RF) – 61.2 IU/ml (IQR 18.5;179.2), mean DAS-28(CRP) – 3, 7±1, 2. All patients received disease-modifying antirheumatic drugs. SCORE, QRisk2 and 2013 ACC/AHA 10 year ASCVD risk and EULAR recommended modified versions were calculated. Patients with SCORE ≥5%, QRisk2 ≥20% and ASCVD risk ≥7.5% were classified as having high CV risk. Carotid intima-media thickness (CIMT) ≥0, 9 mm and/or carotid plaques detected by ultrasonography were used as the gold standard test for high CV risk. p<0.05 was considered significant. Results: The median SCORE, QRisk2 and ASCVD were 2.2% (IQR 0.6;4.9), 10.2% (3.4;19.2) and 4.9% (1.5;12.8) respectively. The proportion of high-risk patients was as follows: 14 (25%), 13 (23%), 24 (43%) for SCORE, QRisk2 and ASCVD. Mean CIMT was 0.76±0.24 mm. US criteria for subclinical atherosclerosis (US+) were found in 27 (48%) pts. Discriminating capacities for the indexes were as follows: AUC 0.723 (CI 95% 0.626–0.821) for SCORE, AUC 0.705 (CI 95% 0.606–0.804) for QRisk2 and AUC 0.837 (CI 95% 0.757–0.917) for ASCVD. The percentages of high-risk patients in US+group were as follows: 13 (48%), 12 (44%) and 21 (78%), respectively, (p<0.05 compared to ASCVD). After multiplying by 1.5 EULAR 2016 mASCVD reclassified 2 (7.4%) and mSCORE – 4 (14.8%) pts from moderate to high risk. Use of lower cut-off values for risk indices (SCORE ≥1%, QRisk2 ≥10% and ASCVD ≥5%) resulted in better detection of US+pts (100%, 85% and 85% respectively). Conclusions: The 2013 ACC/AHA 10 year ASCVD risk estimator is better than the SCORE and QRisk2 indices for the detection of high CV risk RA patients. Adjustment of the threshold may be a better modification of risk scales than use of the EULAR multiplier factor. References: [1] Agca R, Heslinga S, Rollefstad S, et al. EULAR recommendations for cardiovascular disease risk management in patients with rheumatoid arthritis and other forms of inflammatory joint disorders: 2015/2016 update. Ann Rheum Dis2017;76(1):17–28. [2] Avina-Zubieta JA, Thomas J, Sadatsafavi M, Lehman AJ, Lacaille D. Risk of incident cardiovascular events in pa- tients with rheumatoid arthritis: a meta-analysis of obser- vational studies. Ann Rheum Dis2012;71:1524–9. Disclosure of Interest: None declared